End-to-end quality of service network design : QoS for rich-media and cloud networks - Szigeti, Tim (Cisco Press, 2013)
"This course will mirror the author's recently released book, End-to-End QoS Network Design, exploring various QoS designs for new applications and technologies, industry standards and platforms (with more than 10 different Cisco product families being represented throughout). Tim Szigeti will supply design recommendations and enable the viewer to confidently and successfully design and deploy QoS across their Cisco networks."--Resource description page.